Capon-like method for direction of arrival estimation Using acoustics vector sensor. (August 2022) - Chen, Feng; Yang, Desen; Zhang, Yi; Li, Song; Mo, Shiqi
Graphical abstract: Abstract: Acoustic vector sensor (AVS) is a kind of sensor widely used in underwater detection. This study found that due to inconsistent received noise power, the acoustic vector sensor generates virtual sources, which could affect the subspace algorithm. To overcome this shortcoming, a Direction-Of-Arrival (DOA) algorithm which is agnostic to the number of sources is proposed. Using the covariance matrix and the power of the scanning source, a reference matrix is constructed, and the maximum eigenvalue characteristics of the reference matrix at different angles are analyzed. Secondly, a novel eigenvalue arrangement is constructed based on the conclusions. Thirdly, the influence of the relevant parameters on the performance of the proposed algorithm is analysed. Finally, the correctness of the theory and the algorithm is verified by the experimental simulation.